Efektivitas Kerja Anak Buah Kapal Pelni - Prasadja Ricardianto; Maroef Akbar; Francis Tantri (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of this study is to analyze leadership, and attachment to the effectiveness of the work of the crew of PT Pelayaran Nasional Indonesia (PELNI). The research survey was conducted on 80 ship crew by groups of observation units sampling technique (cluster observation units) or Cluster Systematic Sampling of the entire population of 377 ship crew on ships anchored at the Port of Tanjung Priok. This study uses quantitative approach with path analysis method. The results show that leadership style, and attachment has a positive and direct effect to work effectiveness. The study is expected to benefit PELNI in a way that through the leadership style of its officers, the employee's attachment will improve the working performance of each ship crew. The novelty of this research is on the application of employee engagement model and the effectiveness of the work of the ship crew on the national shipping industry. The outcome of this study is that any changes on the ship officers’ leadership style quality and the attachment will increase directly to the work effectiveness of PELNI's ship crew.